Exosomes Derived From Dendritic Cells Infected With Toxoplasma gondii Show Antitumoral Activity in a Mouse Model of Colorectal Cancer - Lu, Jinmiao; Wei, Nana; Zhu, Shilan; Chen, Xiaoyu; Gong, Haiyan; Mi, Rongsheng; Huang, Yan; Chen, Zhaoguo; Li, Guoqing (Frontiers in Oncology, 2022)
Pathogen-based cancer therapies have been widely studied. Parasites, such as Toxoplasma gondii have elicited great interest in cancer therapy. Considering safety in clinical applications, we tried to develop an exosome-based immunomodulator instead of a live parasite for tumor treatment. The exosomes, called DC-Me49-exo were isolated from dendritic cells (DCs) infected with the Me49 strain of T. gondii and identified. We assessed the antitumoral effect of these exosomes in a mouse model of colorectal cancer (CRC). Results showed that the tumor growth was significantly inhibited after treatment with DC-Me49-exo. Proportion of polymorphonuclear granulocytic bone marrow-derived suppressor cells (G-MDSCs, CD11b+Ly6G+) and monocytic myeloid-derived suppressor cells (M-MDSCs, CD11b+Ly6C+) were decreased in the Me49-DC-exo group compared with the control groups in vitro and in vivo. The proportion of DCs (CD45+CD11c+) increased significantly in the DC-Me49-exo group. Levels of interleukin-6 (IL-6) and granulocyte-macrophage colony-stimulating factor (GM-CSF) significantly decreased after treatment with DC-Me49-exo. Furthermore, we found that DC-Me49-exo regulated MDSC count mainly by inhibiting the signal transducer and activator of transcription (STAT3) signaling pathway. These results indicated that exosomes derived from DCs infected with T. gondii could be used as part of a novel cancer therapeutic strategy by reducing the proportion of MDSCs.